Analisis Perancangan Sistem Anjungan Pendaftaran Mandiri Untuk Pemilihan Dokter dan Waktu Pelayanan di Rumah Sakit: Literature Review - Nerissa Adha Andrania; Daniel Happy Putra; Noor Yulia; Adi Widodo (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Self-Registration Patient is a health service facility related to registration independently by patients who are provided by the machine. The purpose of this study is to identify what the user/patient needs and also to analyze the design for the doctor's appointment in hospitals. The method used a literature review approach through a database of Google Scholar obtained by 6 national-based journals, while Google Patent obtained 4 international-based patents. The results are related to the process of basic needs that will be used by users/patients such as QR Barcodes; touch screen monitors; Numpad and mouse; speakers; receipt printing machine; SEP paper printing; and CPU. The design supported by distribution model system such as; Entity-Relationship Diagram (ERD); Data Flow Chart (DFD); Use Case Diagram (UCD); flow chart, and interface design. In conclusion, the research could help the hospital's needs and also the patients, including knowing the latest status of patients, making appointments according by intended polyclinic, doctors, and time visits based on doctor's time schedule. It is also could print SEP as well as the pharmacy queue number receipt after being examined. The system is also expected to reduce long queues at the Outpatient Registration Place (TPPRJ), especially for BPJS Insurance users.